PENGARUH MINAT BACA DAN PERAN DOSEN PEMBIMBING TERHADAP KEBERHASILAN PENULISAN TUGAS AKHIR - Damanik, Bahrudi Efendi (Idaarah: Jurnal Manajemen Pendidikan, 2018)
Abstract: The purpose of the study is to examine whether there is an influence of reading interest and the role of supervisors partially or simultaneously on the success of writing the final assignment. The research was conducted at AMIK Tunas Bangsa Pematangsiantar by taking a sample of 78 people from 369 population populations using calculations using Slovin formula. The method used is the survey method and data collection carried out through observation, interviews, and distributing questionnaires using a Likert scale as a measuring device. The sampling technique using purposive sampling is a sampling technique of data sources with certain considerations, the analytical technique used is multiple lenier analysis techniques. In analyzing the data used several descriptive analysis techniques to determine the distribution of respondents’ answers to the overall concept being measured, quantitative analysis using numbers and calculations with statistical methods. The results of the analysis show that partial reading interest has a positive and significant effect on the success of the final assignment, tcount> t table (3.167> 1.991), the role of partial supervisor is positive and significant effect on the success of the final assignment, tcount> t table (2.915> 1.991), reading interest and the role of supervisors simultaneously have a positive and significant effect on the success of the final assignment where the value of Fcount> Ftable is (20,094> 3,12).